2016
DOI: 10.1515/znb-2016-0121
|View full text |Cite
|
Sign up to set email alerts
|

Morpholinium hydrogen sulfate (MHS) ionic liquid as an efficient catalyst for the synthesis of bio-active multi-substituted imidazoles (MSI) under solvent-free conditions

Abstract: Morpholinium hydrogen sulfate as an ionic liquid was employed as a catalyst for the synthesis of a biologically active series of multi-substituted imidazoles by a four-component reaction involving the combination of benzil with different aromatic aldehydes, ammonium acetate, and 1-amino-2-propanol under solvent-free conditions. The key advantages of this method are shorter reaction times, very high yield, and ease of processing. Furthermore, the resulting products can be purified by a non-chromatographic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…[32] An equimolar concentrated H 2 SO 4 was added slowly in a drop wise manner into this the flask at 0°C.After that, the reaction mixture was allowed to be stirred and heated at 80°Cfor 12 hours.…”
Section: General Methods For Synthesis Of Phs Ionic Liquidmentioning
confidence: 99%
“…[32] An equimolar concentrated H 2 SO 4 was added slowly in a drop wise manner into this the flask at 0°C.After that, the reaction mixture was allowed to be stirred and heated at 80°Cfor 12 hours.…”
Section: General Methods For Synthesis Of Phs Ionic Liquidmentioning
confidence: 99%
“…By comparing the biological activity of the present synthesized compounds with those reported in the literature, we found that compound 5c which contains the 2‐(4‐fluorophenyl)imidazole moiety shows higher activity than compound 5c which contains the 2‐(4‐chlorophenyl)imidazole moiety. This may be due to the higher electronegativity of fluoride atom at para position than chloride atom.…”
Section: Resultsmentioning
confidence: 63%
“…This may be due to the higher electronegativity of fluoride atom at para position than chloride atom. Also, the newly synthesized compounds 5 h and 5i containing the 1‐( N ‐dimethylaminopropyl)imidazole moiety show more potent activity than compound 5d which has the isopropanol moiety instead. Moreover, compound 5f has a high biological activity which is attributed to the presence of a hydroxyl group in meta and para positions.…”
Section: Resultsmentioning
confidence: 95%
“…However, restricting the search to compounds with isopropanol substituents on N1 reduces the hits to three reports of our work to produce compounds with 4-benzoic acid (Jasinski et al, 2015) and 4-chloro- (Mohamed et al, 2017) and 2,5-dichloro-substituents (Akkurt et al, 2015) at the 2-position of the imidazole ring. A more recent paper, detailing the use of ionic liquids as catalysts for the preparations of similar compounds, also reports analogues with an unsubstituted phenyl ring and a 2,5-dimethoxy substituted benzene ring at the 2-positions (Marzouk et al 2017). Other closely related derivatives have ethanol (Mohamed et al, 2013a) and n-propanol substituents on the N1 atom (Mohamed et al, 2015).…”
Section: Database Surveymentioning
confidence: 99%